1994
DOI: 10.1002/macp.1994.021950733
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies on copolymers having pendant monosaccharides

Abstract: Copolymers having pendant monosaccharide groups were synthesized by copolymerizing 2-(glucosy1oxy)ethyl methacrylate (GEMA, l), with methyl methacrylate (MMA) or styrene (St).The surface characteristics of the copolymer films were investigated by means of contact angle measurements, X-ray photoelectron spectroscopy (XPS), and protein adsorption. The surface free energy of the GEMA/St copolymer films was constant in the range of a GEMA content from 10 mol-To to 60 mol-To. Insertion of GEMA of over 60 mol-To, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…The signals of e 1 s and O 1 s of poly(GEMA-coSt) microspheres with f = 10 as a typical instance are illustrated in Figure 5. The e 1 s spectra of the polymer microspheres coincide in position with those of the GEMA/St copolymer films prepared by Nakamae et al 19 Taking into account the results in the literature, 19 the carbon signals at 285 and 291 eV are ascribable to the methylene group and the shake-up satellite attributable to the n-n* molecular orbital transition of the benzene ring. The signals at 287 and 289eV are assigned to the e-O-and e = 0 originated from the GEMA moiety.…”
Section: Xps Measurement Of Particlessupporting
confidence: 74%
See 3 more Smart Citations
“…The signals of e 1 s and O 1 s of poly(GEMA-coSt) microspheres with f = 10 as a typical instance are illustrated in Figure 5. The e 1 s spectra of the polymer microspheres coincide in position with those of the GEMA/St copolymer films prepared by Nakamae et al 19 Taking into account the results in the literature, 19 the carbon signals at 285 and 291 eV are ascribable to the methylene group and the shake-up satellite attributable to the n-n* molecular orbital transition of the benzene ring. The signals at 287 and 289eV are assigned to the e-O-and e = 0 originated from the GEMA moiety.…”
Section: Xps Measurement Of Particlessupporting
confidence: 74%
“…Nakamae et al reported that when copolymer films composed of GEMA and St were immersed in hot water, the surface became more hydrophilic because the GEMA unit migrated to the surface in order to minimize the surface free energy of the copolymer films. 19 The content of the GEMA moiety located on the surface of particles is, therefore, considered to be much larger in the emulsion than that of content measured by XPS for the air-dried particles. The monomer reactivity ratios, r 1 and r 2 , obtained by the free radical copolymerization of GEMA (M 1 ) and St (M 2 ) in DMF are 1.49 and 0.11 24 (or 1.50 and 0.50 19 ), respectively.…”
Section: Xps Measurement Of Particlesmentioning
confidence: 96%
See 2 more Smart Citations
“…52 We synthesized a variety of carbohydrate polymers by copolymerizing a monomer with pendant glucose (2-glucosyloxyethyl methacrylate: GEMA) and hydrophilic or hydrophobic monomers and examined their unique surface properties under various conditions. [53][54][55][56][57][58] Furthermore, complex formation between Con.A and polymers with pendant glucose (PGEMA) was investigated to design a glucose-responsive polymer. 59 When Con.A was added to a buffer solution containing PGEMA, the solution became turbid due to multiple associations between PGEMA and Con.A.…”
Section: Glucose-responsive Hydrogelsmentioning
confidence: 99%